Rekontruksi Laporan Keuangan Distributor Molreng Jember Berdasarkan SAK EMKM - Almira Ayu Octavia; Rochman Effendi; Whedy Prasetyo (Universitas Jember, 2019)
This study discusses the suitability and financial reporting of Molreng Jember Distributors based on SAK EMKM. The method used by researchers is a qualitative method. This research is a case study with the object of research on the financial statements of Molreng Jember Distributors who have not yet applied the SAK EMKM-based financial reporting. Data retrieval is done by interview and documentation. This study shows that Molreng Jember Distributors only make simple records, considering the lack of understanding in making financial reports. Molreng Jember Distributors only record income and borrowing in order to obtain the final result in the form of profit. Financial reports for Molreng Jember Distributors can be accessed by the owner to find out how the business actually is so that they can determine the selling price for the following year. Keywords: Financial statements, UMKM, SAK EMKM